Producción de metano en reactores monofásico y bifásico a partir de agua modelada de la Industria de Café soluble - Laz Mero, Mabel Leonela (2020)
The objective of this research was to establish the production of methane in reactors with a Monophasic System (SM) and a Biphasic System (SB) using modeled water from the soluble coffee industry as a substrate, with a chemical oxygen demand (COD) of 7,5 g / L, considered as a waste with a high organic load. The laboratory tests were performed in reactors fitted with an Upflow Anaerobic Filter (UAF), evaluating parameters of: pH, relationship between volatile fatty acids and alkalinity (FOSTAC), COD removal, concentration and methane yield, applying standardized methods for the analysis of wastewater described by APHA & WPCF, 2012. In the yield variable, the SM showed average values of 0,15 dm³ CH₄ / gDQO in comparison to those exhibited by the SB with average values of 0,26 dm³ CH₄ / g COD, the operating ranges of the SB were: pH (6,38-8, 0), FOSTAC (0,42-0,60), AGV (160-423mg / l), COD removal (61-85%); where it was statistically verified that the methane productions in the evaluated systems differ significantly (p <0,05), evidencing that the mean methane production values increased by 70% in relation to the SM.